Assessment of local earthen bricks in perspective of physical and mechanical properties using Geographical Information System in Peshawar, Pakistan. (December 2020) - Ali, Mujahid; Room, Shah; Khan, Muhammad Imran; Masood, Faisal; Ali Memon, Rizwan; Khan, Razaullah; Memon, Abdul Muhaimin
Abstract: Due to good quality of soil in the Peshawar region (North-West of Pakistan) and the expertise of the local labors in brick's production, bricks of this region is more popular in the country and exported to different provinces of the country as well as to Afghanistan. There are approximately 450 brick kilns in Peshawar and their production per day/brick-kiln is around 75, 000 bricks; hence the daily production is about 3.4 Million. This study examines the physical and mechanical properties of local earthen clay bricks and their production in Peshawar city. There is a lack of relevant data about the excellence of locally made bricks and the selection of proper bricks kiln for any intended use of suitable bricks. Initially, out of 450 brick kilns, the location of 254 were noted through the Global Positioning System (GPS) to represent their location on google map using their coordinates. However, the whole area was distributed in four zones from which 50 brick kilns were selected from all zones. The analysis shows that bricks from all the selected kilns have acceptable engineering properties fulfilling American Society for Testing and Material (ASTM C67) guidelines. The mechanical properties of 1st class bricks have large variability, showing less porosity (19%), high compressive strength (CS) up to 24.27 MPa, and low water absorption (WA) rate of 11.9%. The CS of 1st class bricks was 56.73% greater than the standard CS whereas, it was 46.2% and 38.88% greater in case of 2nd and 3rd class bricks, respectively. A strong correlation was found in CS and WA, which was 76.83% in 1st class bricks and 77.44% and 85.29% in the 2nd and 3rd class bricks. Using Quantum Geographical Information System (QGIS), the results obtained along with kiln coordinates and other required parameters have been presented graphically. Inventory of the brick kilns for the selected zones has been developed using QGIS, which can be used by various relevant departments, contractors, and environmental protection agencies.